The interplay between irrigation and fruiting on branch growth and mortality, gas exchange and water relations of coffee trees - Almeida, Wellington L. (2021)
The overall coordination between gas exchanges and plant hydraulics may be affected by soil water availability and source-to-sink relationships. Here we evaluated how branch growth and mortality, leaf gas exchange and metabolism are affected in coffee (Coffea arabica L.) trees by drought and fruiting. Field-grown plants were irrigated or not, and maintained with full or no fruit load. Under mild water deficit, irrigation per se did not significantly impact growth but markedly reduced branch mortality in fruiting trees, despite similar leaf assimilate pools and water status. Fruiting increased net photosynthetic rate in parallel with an enhanced stomatal conductance, particularly in irrigated plants. Mesophyll conductance and maximum RuBisCO carboxylation rate remained unchanged across treatments. The increased stomatal conductance in fruiting trees over nonfruiting ones was unrelated to internal CO2 concentration, foliar abscisic acid (ABA) levels or differential ABA sensitivity. However, stomatal conductance was associated with higher stomatal density, lower stomatal sensitivity to vapor pressure deficit, and higher leaf hydraulic conductance and capacitance. Increased leaf transpiration rate in fruiting trees was supported by coordinated alterations in plant hydraulics, which explained the maintenance of plant water status. Finally, by preventing branch mortality, irrigation can mitigate biennial production fluctuations and improve the sustainability of coffee plantations.